Ecological Factors in Changing Economy and Social Organization Among the Rupert House Cree - Knight, Rolf (Department of the Secretary of State, 1968)
A brief ethnographic study done for the National Museum of Canada in 1961-62 focusing on the then continuing economic importance of hunting and trapping for the native people of the region. –Author's description
OCLC: 623481878